A prospective analysis examining frailty remission and the association with future falls risk in older adults in England. (21st February 2023) - Davies, Katie; Maharani, Asri; Chandola, Tarani; O'Neill, Terence W; Todd, Chris; Pendleton, Neil
Abstract: Background: Previous research has shown older adults experience dynamic changes in frailty status. This study aimed to determine the occurrence of sustained frailty remission and how remission is associated with falls risk. Methods: Participants who contributed data to the analysis were in the English Longitudinal Study of Ageing from Waves 1 to 8 (2002–2017). Frailty was defined across waves using the frailty index and categorised into robust, pre-frail and frail. We classified participants who improved their frailty category from Wave 1 (2002) to Wave 2 (2004) and sustained/improved category again into Wave 3 (2006) and compared them with those who were either robust or frail across Waves 1–3. Cox proportional hazard modelling was used to determine the risk of incident falls reported at Waves 4–8, with results expressed as hazard ratios and 95% confidence intervals. Results: Of 2, 564 participants, 389 (15·2%) improved frailty category and sustained this during Waves 2–3, 1, 489 (58·1%) remained robust and 686 (26·8%) remained frail during Waves 1–3. During the 10-year period (Waves 4–8), a total of 549 participants reported a fall. Compared with those who remained frail during Waves 1–3, those who with sustained frailty remission had a lower risk of future falls (HR 0·41; 95% CI = 0·36–0·45). Conclusions: Frailty remission is possible and can be sustained across 5 years. There is a lower risk of future falls in those who sustain frailty remission compared with those who remain frail.